The development of infantile nystagmus. Issue 5 (13th November 2014) - Theodorou, Maria; Clement, Richard; Taylor, David; Moore, Anthony
Abstract : Purpose: To obtain quantitative measurements of the development of infantile nystagmus in children. This task is challenging because the eye movement recording requires some cooperation. Method: The oscillations in short duration eye movement recordings were identified by the method of close returns and the characteristics of the saccadic main sequence were used to calibrate the oscillations. These techniques were applied to 11 subjects, aged 0–4 years, who were all tested on more than one occasion. Results: The range of waveforms could be described by a sum of asymmetric pendular and pseudocycloid components. The amplitude of the nystagmus decreased from 0 to 1.5 years and then increased again. The foveation associated with the nystagmus increased up to 1.5 years and then remained approximately constant. The average visual acuity of the subjects increased steadily from 0 to 4 years. Conclusions: These findings imply that developmental waveform changes are associated with improved visual acuity but only until 1.5–2 years of age.